2021
DOI: 10.1175/jcli-d-20-0573.1
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Meridional Modes without Equatorial Pacific Influence

Abstract: Investigating Pacific Meridional Modes (PMM) without the influence of tropical Pacific variability is technically difficult if based on observations or fully coupled model simulations due to their overlapping spatial structures. To confront this issue, the present study investigates both North (NPMM) and South PMM (SPMM) in terms of their associated atmospheric forcing and response processes based on a mechanically decoupled climate model simulation. In this experiment, the climatological wind stress is prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Specifically for the latter, the POGAs capture the less effective forcing role of AL variability in the PMM (Figures 1c and S3c). In addition, POGA results show the significant forcing roles of NPO and NPT variabilities in the PMM (Figures 1f, 1l and , ), consistent with previous findings (Amaya, 2019; Chiang & Vimont, 2004; Zhang et al., 2021). All the above results are significant at the 99% confidence level.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically for the latter, the POGAs capture the less effective forcing role of AL variability in the PMM (Figures 1c and S3c). In addition, POGA results show the significant forcing roles of NPO and NPT variabilities in the PMM (Figures 1f, 1l and , ), consistent with previous findings (Amaya, 2019; Chiang & Vimont, 2004; Zhang et al., 2021). All the above results are significant at the 99% confidence level.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have shown that the leading atmospheric driver of changes in trade wind strength is related to the North Pacific Oscillation (NPO; Rogers, 1981;Walker & Bliss, 1932), which is the second empirical orthogonal function (EOF) mode of sea level pressure (SLP) variability over the North Pacific. Its southern lobe over the Hawaiian Islands can effectively initiate the WES feedback and thus the PMM (Chiang & Vimont, 2004;Zhang et al, 2021). In addition to the NPO, a recent study by Zhang et al (2021) identified a new North Pacific atmospheric mode contributing to forcing the PMM, termed the North Pacific Tripole (NPT), which emerges as the fourth SLP EOF mode.…”
mentioning
confidence: 99%
“…[21] Owing to the similarity between the SPMM and ENSO, studies on the meridional modes have devoted substantial efforts to remove the ENSO signals, for instance, by adopting linear regression to separate the cold tongue index from the reanalysis dataset (Chiang and Vimont 2004;Min et al 2017); by coupling a slab ocean mixed layer model to remove oceanic dynamics, thus pulling apart the Bjerknes feedback and Rossby wave adjustments (Zhang et al 2014a); by prescribing climatological winds which have no anomalous ENSO-related forcing to the ocean model (Larson et al 2018;Zhang et al 2021). We do not attempt to remove the oceanic dynamics, and the ENSOlike signature before the regime shift is unsurprising.…”
Section: Atmospheric Fields In Association With the Spmm Indexmentioning
confidence: 99%
“…[36] The present study focused on the interannual variance of the SPMM due to a lack of reliable multidecadal SST time series. Previous studies, however, have underlined the critical role of stochastic forcing from weather systems in the Southern Hemisphere (Okumura 2013;Liguori and Di Lorenzo 2019;Zhang et al 2021), in tandem with a subsurface temperature anomaly driven by the subtropical shallow meridional subduction in the SPMM region (Gu and Philander 1997;Imada et al 2016), on driving decadal ENSO-like variability, IPO. proposed a nonlinear ENSO warming suppression (NEWS) mechanism to show that La Nina-like mean-state warming is also a possible candidate in a warm climate because of the nonlinear rectification effect (Jin et al 2003).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation